Microbial Electrochemical Sensors for Anaerobic Digestion Process Control – Performance of Electroactive Biofilms under Real Conditions. Issue 4 (8th February 2018) - Kretzschmar, Jörg; Böhme, Paul; Liebetrau, Jan; Mertig, Michael; Harnisch, Falk
Abstract: The autonomous growth of Geobacter sp.‐dominated biofilms on electrodes and their sensitivity on volatile fatty acids (VFAs) allows their application as biosensor. In this study, the implementation of a microbial electrochemical sensor in the anaerobic digestion (AD) process is reported. The amperometric sensor signal follows the acetate concentration profile in the AD process. Yet, the sensor's stability is impaired by the process conditions. Therefore, potential biofilm inhibitors are individually examined, i.e., high salt and NH4 + concentrations as well as fumarate as potential alternative electron acceptor. The results show no influence of high salinity on the signal, whereas ammonia at a concentration ≥ 5 g L −1 NH4 + acts as inhibitor, and fumarate is used as substrate for current generation. Abstract : A microbial electrochemical sensor for the quantification of volatile fatty acids is integrated in a real anaerobic digestion process. The sensor signal correlates with the acetate concentration in the process but the sensor stability is affected by the process conditions. Potential inhibitors in the anaerobic digestion process are examined to explain the observed loss of function.